Automatic identification of vehicles from single view - Lim, Nicholas Shin Cheong (Nanyang Technological University, 2022)
Transportation has always been part and parcel of our daily lives. Getting from one place to another and getting there safely in one piece is two different sides of a coin. Be it public transport, private hire or your own vehicle, safety of our well-being is always paramount. With the increasing number of vehicles on the road, your safety might be dependent on the other drivers, no matter how safe you are. Thus, with the use of AI applications to perceives the vehicle’s surrounding environment, identify and keep track of multiple objects (moving or stationary), we are able to reduce the possibilities of tragedies from happening.